Роль адаптивності для сучасних WEB-сайтів - Надточій, Д. В. (ХНУРЕ, 2022)
Today, more and more people use smartphones to search the Internet. That is why it is important that the website is adaptive. An adaptive website adapts to the screen sizes of any device while maintaining content and functionality, the mechanism of user interaction is faster and more efficient, and usability is improved. As a result, the target audience is expanding.
Keywords: website; адаптивність сайту